Keefektifan Aplikasi Podcast Spotify dalam Pembelajaran Keterampilan Menyimak pada Siswa Kelas X SMA PGRI Larangan - Novia Shafa Dwijayanti; Dyah Werdiningsih (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Learning media is needed by teachers so that students can receive information or messages well. The Spotify application used is a podcast for listening skills in students. The purpose of this study was to determine the effectiveness of the Spotify podcast application as a medium for learning listening skills for students in the X grade of PGRI Prohibition High School. The research method used is the qualitative and quantitative mixture method. The bound variable is PGRI Prohibition High School X class students. Data collection techniques through interviews and distributing questionnaires. The data analysis technique uses a Likert scale. The results of the study on the learning medium in the form of podcast application Spotify obtained four answer indicators, namely (1) strongly agree obtained a score of 203, (2) agree obtained a score of 373, (3) disagree got a score of 37, and (4) strongly disagree got a score of 6. Therefore, this application is worth using when learning listening skills in the classroom.